(untitled) (Philological Studies, 2019)
This article deals with the paronyms in the Macedonian standard language, and its aim is to examine the paronyms motivated from different noun bases. The research is qualitative and has a descriptive design. The corpus of the paronyms is excerpted from Tolkoven rechnik na makedonskiot jazik (2003) [Monolingual Dictionary of the Macedonian language], and the examples of their usage from various electronic sources. The methods used for processing the data and gaining conclusions are analysis, synthesis and comparison. The analyzed material indicates that, in the adjective paronyms pair in standard Macedonian, one of the adjective is derived from an unmotivated, and the other frоm a motivated noun, and that there are some dilemmas regarding their meaning.